RELATIONSHIP BETWEEN SOME SOIL PROPERTIES AND WHEAT AND BARLEY PRODUCTIVITY IN ALLUVIAL SOIL AT WASET GOVORNORATE - & Mohamed, Ahmed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was conducted to show the relationship between some soil properties and land productivity from wheat and barely crops. The study area located in Al-Muwafaqia – Waset Govornorate / central of Iraq. General soil data were collected from previous soil survey work done in 1992 ,and new soil samples from the same profile location were collected to determine some soil properties . The actual land productivity from Wheat and Barely crops were collected from the same selected sites . The results indicate some variations in land productivity for the selected crops and wheat productivity was higher than barely productions. Wheat productivity was ranged from 2000 to 2350 kg.ha-1 with mean of 2118.75 Kg.ha-1, while barely productivity ranged from 2000 to 2350 kg.ha-1 with mean of 20187.5 kg.ha-1. All soil properties show a positive and significant correlation with crops productivity except soil salinity which shows a negative correlation. Soil salinity considered as the most limiting factor for crops production as well as bad land management practices and the impact of the socioeconomic condition.